2022-RA-904-ESGO Vaginal cuff brachytherapy in intermediate and intermediate high risk endometrial cancers after hysterectomy: clinical outcomes. (20th October 2022) - Cordoba, Abel; Escande, Alexandre; Scournec, Cyrielle; Narducci, Fabrice; Martinez, Carlos; Leblanc, Eric; Hudry, Delphine; Pasquesoone, Camille; Taieb, Sophie; Mirabel, Xavier; Lartigau, Eric; Le Tinier, Florence
Abstract : Introduction/Background: Vaginal cuff brachytherapy is the recommended adjuvant treatment for patients operated on for endometrial cancer classified as intermediate risk for recurrence. We evaluated the results of high-dose-rate brachytherapy after radical surgery. Methodology: This was a retrospective study of all patients treated consecutively at Oscar Lambret center between 2012 and 2015 by hysterectomy and adjuvant cuff vaginal brachytherapy. Four fractions of 6.2Gy each to superior third of vaginal and 5 millimetres deep were prescribed. We analysed local (vaginal) control, overall survival, recurrence-free survival, and acute and late toxicities. Local control was assessed by taking into account the cumulative incidence of local recurrence estimated by the competitive risk method. Survival analyses were performed using the Kaplan-Meier method. Results: We included 250 patients; 208 were considered to be at high intermediate risk of recurrence postoperatively. After a median follow-up of 56 months, the cumulative incidence of local recurrence was 4.8% at 3 years (95% CI: 2.8–8.3) and 6.8% at 5 years (95% CI; 4.8–12.6). The 5-year overall survival was 86.2% (95% CI: 80.6–90.3) and the 5-year recurrence-free survival was 77.5% (95% CI: 71.1–82.7). Acute toxicities are occurred in 20 patients (8%), of whom 2 patients had grade ≥3 toxicities. One patient (0.4%) had late toxicity of grade ≥3. Conclusion: Our results show a local recurrence rate that is 3% to 4% higher than that found in the literature, largely explained by the different selection of our patients. The overall survival remains similar to published data, suggesting the effectiveness of salvage treatments and the low impact of local recurrence on survival. The integration of molecular data with current clinical and pathological risk factors should allow a more accurate selection of patients who will benefit from adjuvant therapy.